Interoperability of Digital Payment Platforms (QRIS) and its Effect on Micro, Small, and Medium Enterprise (MSME) Transaction Costs - Isma Nurrokhim; Yuni Astriana Khamidah; Izzatun Maghfirah; Nenny Syahrenny; Nuzul Ibnu Hajar (CV. Get Press Indonesia, 2025)
The global shift toward digital payment platforms holds significant potential for Micro, Small, and Medium Enterprises (MSMEs), yet the fragmentation of these systems often creates costly interoperability barriers that impede operational efficiency and constrain growth. This research quantitatively assesses how the standardization initiative, specifically Indonesia’s Quick Response Code Indonesian Standard (QRIS), influences MSME transaction costs. Utilizing a quantitative design, the study synthesized secondary transactional data from Bank Indonesia (BI) and the National Payment Corporation of Indonesia (NPCI) (2019–2025) with primary survey data collected from approximately 1,200 MSMEs nationwide. Key variables analyzed included interoperability indices, actual transaction costs, operational efficiency, and adoption metrics. The findings conclusively demonstrate that QRIS interoperability leads to a quantifiable 3% to 5% reduction in transaction costs, drives a substantial increase in digital transaction volumes, and facilitates market expansion for MSMEs. Furthermore, operational efficiency and user trust were identified as critical factors mediating the positive relationship between interoperability and cost reduction. These results offer actionable evidence for policymakers and financial stakeholders dedicated to fostering MSME financial inclusion and catalyzing inclusive economic growth via robust digital infrastructure. Future studies should prioritize longitudinal analyses of interoperability’s long-term effects and effective strategies for bridging technological and literacy divides.